2014
DOI: 10.1080/15287394.2014.955834
|View full text |Cite
|
Sign up to set email alerts
|

Auranofin Promotes Mitochondrial Apoptosis by Inducing Annexin A5 Expression and Translocation in Human Prostate Cancer Cells

Abstract: Auranofin is a lipophilic gold compound with anti-inflammatory and immunosuppressive properties. This compound also exerts antiproliferative effects in several human cancer cell lines. Although auranofin induces apoptosis in human cancer cells, the underlying mechanisms remain unclear. This study investigated auranofin-mediated inhibition of cell growth and induction of mitochondrial apoptosis in PC3 human prostate cancer cells. Treatment with auranofin significantly inhibited cell viability with an IC50 value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…www.nature.com/scientificreports www.nature.com/scientificreports/ After glucose depletion, pIRES cell death was caused by mild necrosis and by early intrinsic apoptosis as documented by the increased percentages of PI -CaspACE + and PI -Annexin V + cells. In this context, phosphatidylserine externalization from the inner to the outer membrane site as requirement for the binding of Annexin V dye has been identified as an early and prominent feature of mitochondrially-mediated apoptosis 14,15 . Therefore, we estimated the increased percentages of PI -CaspACE + and PI -Annexin V + cells following glucose depletion as indicator of an intrinsic, mitochondrially-mediated apoptosis path where phosphatidylserine externalization is accompanied by the activation of caspases.…”
Section: Discussionmentioning
confidence: 99%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ After glucose depletion, pIRES cell death was caused by mild necrosis and by early intrinsic apoptosis as documented by the increased percentages of PI -CaspACE + and PI -Annexin V + cells. In this context, phosphatidylserine externalization from the inner to the outer membrane site as requirement for the binding of Annexin V dye has been identified as an early and prominent feature of mitochondrially-mediated apoptosis 14,15 . Therefore, we estimated the increased percentages of PI -CaspACE + and PI -Annexin V + cells following glucose depletion as indicator of an intrinsic, mitochondrially-mediated apoptosis path where phosphatidylserine externalization is accompanied by the activation of caspases.…”
Section: Discussionmentioning
confidence: 99%
“…Auranofin as an inhibitor of TrxR has an anti-inflammatory effect (17) and can treat rheumatoid arthritis (18). In addition, auranofin shows anticancer effects in ovarian, prostate, breast and lung cancer cells (14,(19)(20)(21). It is also reported that many cancer cells contain high level of TrxR expression (6,22).…”
Section: Discussionmentioning
confidence: 99%
“…Of them, PAI-2 was increased in annexin A5 knockdown cells and was decreased in annexin A5-overexpressing cells. Previous study revealed that auranofin increases annexin A5 expression and translocation into mitochondria to induce apoptosis through oligomerization of VDAC in PC-3 cells (Park and Chun, 2014). Hence, we treated auranofin to induce annexin A5-mediated apoptosis and observed the PAI-2 level resulting in reduction of PAI-2 expression in a concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Phase I/II clinical trials of auranofin to treat chronic lymphocytic leukemia has been completed (Liu et al ., 2014; Clinicaltrials.gov, 2016). Moreover, our recent study suggested that auranofin leads to annexin A5 expression and translocation into mitochondria causing mitochondrial apoptosis through VDAC oligomerization in human prostate cancer cells (Park and Chun, 2014). …”
Section: Introductionmentioning
confidence: 99%